Proceedings of CARPA9 : ecological design and performance pedagogies : sustainable practices and interdisciplinary acts in a climate changed world - (:unkn) unknown (Taideyliopiston Teatterikorkeakoulu, 2026)
From 28th to 30th August 2025, 134 participants from 25 countries gathered to discuss the theme of the 9th Colloquium on Artistic Research in the Performing Arts (CARPA9), Ecological Design and Performance Pedagogies – Sustainable Practices and Interdisciplinary Acts in a Climate Changed World. The urgency of the theme of this colloquium was reflected in the unprecedented number of intelligent, insightful, and caring proposals, to the extent that the conference committee could only accept about 50% of proposals due to practical constraints of time and space. The premise for CARPA9 was to explore pedagogical approaches to, in, and for performance making in a climate changed world. In writing our call, the conference committee envisioned discussions and interventions around questions about how to move towards more ecologically and socially sustainable performing arts practices in higher education and university pedagogy. As a platform, CARPA9 thus brought together different perspectives and concerns around understanding and enacting climate justice in performing arts training and research.
Preface Introduction/ Hanna Järvinen & Liisa Ikonen Closing Notes on CARPA9 / Tanja Beer, Natalie Lazaroo & Linda Hassall How this book is organised Strand I Ecological Design Practices How slow can we go? Staging sustainable spaces in the age of burnout / Anna Chrtková Investigating the Theatre Green Book in Education: A reflection of research-informed practice in the UK / Katy Downton Head seeks hand: Regenerative artistic research in costume design / Carly Everaert Maadtoe and performance / Marija Griniuk The recuperative potential of sound: Audio pedagogy and greening media practice / Gretchen Jude Eating, touching, and tap dancing in the garden / Oona Leinovirtanen Paper, plants, and performance: Reapproaching scenography by listening to ancestral knowledge / Hiroko Oshima Designing The Trials: Sustainable design practices in an educational setting / Snežana Pešić Costuming the collapse – Threads of inquiry / Rachel Young Strand II Ecological Performance Making Hyperwithin: A shy dramaturgy in shadowtimes / Anne-Lise Brevers Electroacoustic performance in urban outdoor – Solar-powered instruments and the emergence of a performance milieu / Marianne Decoster-Taivalkoski, Alejandro Olarte & Pascale Weber The vegetal witness: Posthuman choreographies of collapse and regeneration through butoh and generative AI / Juliana España Keller Aesthetic responses to crisis: Jola masquerades / Aldith Gauci Thermofilia: Witnessing the microbial through hot yoga fermentation / Riina Hannula & Kaajal Modi Three embodied techniques for creating and reflecting on mixed reality performance / Marika Hedemyr On more sustainable performance design, education and the future skills in a world of polycrisis / Raisa Kilpeläinen & Milla Martikainen Heterarchical creation – A way to approach a process of performance making as an ecosystem / Monika Klimaitė-Daunienė Mundane matters – "Use what you have" and "politics of the mundane" as tools for facilitating resource-conscious performance art pedagogy / Joonas Lahtinen The choreographic force of matter: Reframing ecodramaturgy / Maedy de Miranda Strand III Ecological Storytelling Unveiling water: Embodied explorations of urban waterscapes / Alba Balmaseda Domínguez Building ecological awareness through ecotheatre: Agency of place / Kitija Balcare Dancing an embodied landscape: An ecosomatic movement workshop / Germain Ducros Plants, stones, and bats: The non-anthropocentric dramaturgy of Chilean director and playwright Manuela Infante / Andrea Franco Marín Nature after nature – Multisensory medley for systems awareness / Jeanette Mueller, Paul Divjak, Alexandra Graupner & Anna-Maria Irgang Performing undisciplined landscapes: A posthuman approach to collective storytelling / Elena Peytchinska & Thomas Ballhausen Keynote Essays Embracing hope and utopia amidst complex eco-social crises / Raisa Foster Listen here: Country as character and ecological whispers in First Nations playwriting and performance / Dylan Van Den Berg.
Keywords: esittävät taiteet; taiteellinen tutkimus; taidepedagogiikka; kestävä kehitys; ilmastonmuutokset; tieteidenvälisyys; performing arts; artistic research; art pedagogy; sustainable development; climate changes; interdisciplinary research